STRATEGI GURU PAI DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK (STUDI KASUS DI KELAS XI SMK QUWEEN Al FALAH MOJO KEDIRI) - Muhammad Shohibul Faza (CENDEKIA: Jurnal Studi Keislaman, 2022)
This research is motivated by the learning methods practiced by PAI teachers at Queen's Vocational High School that seem unattractive, so that it has an impact on student learning interest which is minimal when teaching and learning activities are carried out. This research uses descriptive qualitative research. The results of this study found that after the teachers changed the learning method by adopting the ideas of Hamzah B. Uno, it was found that there was an increase in the learning interest of the Queen Vocational High School students. The strategies in question are: an organizational strategy, which includes the use of LKS books, textbooks and the internet. Delivery strategy, which includes the use of inquiry learning strategies and lecture, discussion, and question and answer techniques. Learning management strategies that include the use of lesson plans and the motivation for the importance of learning PAI. The impact of implementing this strategy on changes in student interest can be seen in: the readiness of students in receiving and preparing the material to be discussed has increased, the attendance of students in participating in learning has also increased, student activity in participating in discussions has increased, the final score of learning outcomes has also increased